The equation of function g(x) in terms of f(x) is g(x) = -3[f(x)].
<h3>What is an equation?</h3>
An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
Given:
genera form of an exponential function is y=aeᵇˣ
Now, equation for f(x) is
f(x) =
Similarly, graph for g(x) is
g(x) =
Comparing the two function a relation can be establish
g(x) = -3[f(x)]
Learn more about Equation here:
brainly.com/question/2263981
#SPJ1
90. To get to this answer, you would multiply 6 X 10 and 3 X 10. You would then add the products: 60 + 30 = 90.
From figure 1: -
From figure 2: 12
From figure 3: 6
From figure 4: -12
From figure 5: -2
Step-by-step explanation:
We need to solve the equation for k.
Solving:
So, the options to be selected are:
From figure 1: -
From figure 2: 12
From figure 3: 6
From figure 4: -12
From figure 5: -2
Keywords: Solving equations
Learn more about Solving equations at:
#learnwithBrainly